Pessary Use in Pelvic Organ Prolapse and Urinary Incontinence - Jones, Keisha A (MedReviews, LLC, 2010)
With the aging population in the United States, there has been a renewed interest in pessaries as a conservative alternative to surgical repair for pelvic organ prolapse (POP). They present a good option for patients who have not completed childbearing, do not desire surgery, or are poor surgical candidates. Long-term pessary use is a safe and effective option for patients with POP and stress urinary incontinence. Although serious side effects are infrequent, insertion and removal of most pessary types still pose a challenge for many patients. Pessary design should continue to improve, making its use a more attractive option.